Pemanfaatan Eceng Gondok (Eichhornia crassipes) Dengan Fermentasi Limbah Tuna (Thunnus albacares) Sebagai Pakan Ikan Nila (Oreochromis niloticus) - Indra Cahyono; Stefanus Takege; Wayan Kantun (Jurnal Riset Diwa Bahari (JRDB), 2025)
This study aims to analyze the effect of the use of water hyacinth (Eichhornia crassipes) fermented with tuna waste (Thunnus albacares) on the growth, feed efficiency, and survival of tilapia (Oreochromis niloticus). Fermentation is carried out using Lactobacillus sp. and Saccharomyces cerevisiae for five days in anaerobic conditions at 35°C. A complete randomized design was used with four fermentation dose treatments (0, 10, 20, and 30 ml/kg feed) as well as three replicas. The results showed that a fermentation dose of 20 ml/kg resulted in the highest absolute weight growth (167.6 ± 11.24 g), the best specific growth rate, the lowest feed conversion ratio (FCR) (0.81), and the highest survival rate (93.3 ± 1.92%). Excessive fermentation doses (30 ml/kg) reduce feed digestibility due to increased crude fiber. Statistical analysis showed a significant influence (p < 0.05) between treatment on growth and feed efficiency. The results indicate that fermentation of fish stomach waste at moderate doses can increase the nutritional value of water hyacinth and support the concept of zero waste aquaculture using environmentally friendly local materials